Incidence, presentation and outcome of toxoplasmosis in HIV infected in the combination antiretroviral therapy era - Martin-Iguacel, Raquel; Ahlström, Magnus Glindvad; Touma, Madeleine; Engsig, Frederik Neess; Stærke, Nina Breinholt; Stærkind, Mette; Obel, Niels; Rasmussen, Line D. (The Journal of infection, 2017)
HIV-associated incidence and prognosis of cerebral toxoplasmosis (CTX) is not well established during later years. From the Danish HIV Cohort Study, we identified 6325 HIV-infected individuals. We assessed incidence, mortality, predictive and prognostic factors of CTX during the pre-combination antiretroviral therapy (pre-cART; 1995–1996) and cART-era (1997–2014). Adjusted incidence rate ratios (aIRR), mortality rate ratios (aMRR) and 95% confidence intervals (CI) were assessed using Poisson regression analysis. CTX IR was 1.17/1000 PYR (95% CI 0.93–1.47). We observed no change in CTX-risk in the first year after HIV-diagnosis, but a substantial reduction in mortality in the first 3 months after CTX diagnosis when comparing the cART-era to the pre-cART-era; {(aIRR: 0.79; 95% CI: 0.37–1.72) (aMRR: 0.15; 95% CI: 0.06–0.38)}. For individuals surviving the first year after HIV-diagnosis or the first 3 months after CTX-diagnosis, IRR and MRR had declined to minimal levels {(aIRR: 0.06; 95% CI: 0.03–0.10); (aMRR: 0.02; 95% CI: 0.01–0.05)}. Three years after CTX-diagnosis 30% of the patients still had neurological deficits. Although, CTX remains an important cause of morbidity and mortality in the cART-era, with high prevalence of neurological sequelae, incidence and mortality has largely declined, especially among those surviving the first year after diagnosis. •Data from the Danish HIV Cohort Study – a nationwide population-based cohort study.•Declining incidence of CTX in the cART-era after surviving the 1st year.•Declining CTX mortality in the cART-era, specially after surviving the first 3 months.•CTX remains an important cause of morbidity and mortality in late presenters.•CTX has an important impact in the patient's later well being and quality of life.